Time to get help? Help-Seeking Process in Latin American Hospital Patients with Alcohol Use Disorder - Conde, Karina (2020)
Alcohol Use Disorder (AUD) is one of the most harmful conditions associated with consumption. Despite a high level of consumption and an elevated number of people living with an AUD, evidence from help-seeking processes in Latin America is scarce and absent in Argentina. This paper aims to describe reasons for delaying and starting help-seeking, the process of problem awareness, and the years elapsed between drinking initiation, problem awareness and help-seeking, as perceived by a clinical, non-random sample of people with AUD (n=51). The most frequent reason for delaying help-seeking was not believing there was a problem. The most frequent motivators for seeking help were having physical or psychological problems due to use and repeated attempts to reduce or stop use. The outcomes of this study can be useful for designing interventions to reduce help-seeking barriers and facilitate access to treatment.